2012
DOI: 10.1177/0363546512438761
|View full text |Cite
|
Sign up to set email alerts
|

The FIFA 11+ Program Is Effective in Preventing Injuries in Elite Male Basketball Players

Abstract: The FIFA 11+ warm-up program is effective in reducing the rates of injuries in elite male basketball players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
194
1
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(215 citation statements)
references
References 47 publications
4
194
1
16
Order By: Relevance
“…For the articles related to descriptive epidemiology and etiology (first and second research question), the Quality in Prognosis Studies (QUIPS) tool was used (Appendix 2), exploring the following six bias domains: study population, study attribution, prognostic factor information, measurement of and controlling of confounding variables, measurement of outcomes, and analysis approaches [10]. Each of the six potential bias domains was rated as having a high, moderate, or low risk of bias [9,11]. We considered a study to have an overall low risk of bias when the methodological risk of bias was rated as low or moderate in all six domains, with at least four domains being rated as low [9,11].…”
Section: Risk Of Bias Appraisalmentioning
confidence: 99%
See 2 more Smart Citations
“…For the articles related to descriptive epidemiology and etiology (first and second research question), the Quality in Prognosis Studies (QUIPS) tool was used (Appendix 2), exploring the following six bias domains: study population, study attribution, prognostic factor information, measurement of and controlling of confounding variables, measurement of outcomes, and analysis approaches [10]. Each of the six potential bias domains was rated as having a high, moderate, or low risk of bias [9,11]. We considered a study to have an overall low risk of bias when the methodological risk of bias was rated as low or moderate in all six domains, with at least four domains being rated as low [9,11].…”
Section: Risk Of Bias Appraisalmentioning
confidence: 99%
“…Each of the six potential bias domains was rated as having a high, moderate, or low risk of bias [9,11]. We considered a study to have an overall low risk of bias when the methodological risk of bias was rated as low or moderate in all six domains, with at least four domains being rated as low [9,11]. A study was rated as having an overall high risk of bias if two or more of the domains were scored as high [9,11].…”
Section: Risk Of Bias Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of knee sprains resulting from noncontact mechanisms was lowest in collegiate football (16.3%) compared with other competition levels. As a result, injury-prevention programs that reduce the risk of noncontact injury [36][37][38] may be most valuable at lower competition levels.…”
Section: Injury Mechanismsmentioning
confidence: 99%
“…Thus, the effects of FIFA11+ on the reduction of injury rates have been elucidated in different sports modalities, such as soccer 21 and basketball 22 . Gomes Neto et al 15 , in their review study, identified that FIFA11+ resulted in a significant reduction in the risk of injury in soccer players.…”
Section: Discussionmentioning
confidence: 99%